PROFIL BERPIKIR KRITIS SISWA KELAS VII DALAM MENYELESAIKAN SOAL CERITA ARITMATIKA SOSIAL DI SMP NEGERI 8 PALU: Critical Thinking Profile Of Seventh-Grade Students In Solving Social Arithmetic Story Problems At SMP Negeri 8 Palu - Fatmawati; Sukayasa; Pathuddin (Universitas Tadulako, 2023)
This study aimed to obtain a description of the critical thinking profile of seventh-grade students in solving social arithmetic story problems at SMP Negeri 8 Palu. This type of research is descriptive with qualitative approach. The subjects of this study where three of class VII A students of SMP Negeri 8 Palu, who each have high, mederate and low mathematical abilities. Subjects were selected based on the consideration that the selected students were communicative students. Data collection techniques in research using critical thinking skills question and interview. Based on the results of research, data analysis and discussion, it can be concluded that the critical thinking profile of class VII students of SMP Negeri 8 Palu in solving problems story on the materials of social arithmetic shape theory that is, the critical thinking profile of students with high mathematical abilities (MS) includes, providing simple explanation, building basic skills, the ability to solve problems and conclude, the critical thinking profile of students with moderate mathematical abilities (ID) includes, providing simple explanations, the ability to solve problems and conclusions and the critical thinking profile of students with low mathematical abilities (AI) only to provide explanations simple.